Inhibitory effect of Selaginella doederleinii hieron on human cytochrome P450 - Lin, Fei; Lin, Xinhua; Wang, Xuewen; Mei, Guanghui; Chen, Bing; Yao, Hong; Huang, Lingyi (Frontiers in Pharmacology, 2023)
Introduction:Selaginella doederleinii Hieron is a traditional Chinese herbal medicine, the ethyl acetate extract from Selaginella doederleinii (SDEA) showed favorable anticancer potentials. However, the effect of SDEA on human cytochrome P450 enzymes (CYP450) remains unclear. To predict the herb-drug interaction (HDI) and lay the groundwork for further clinical trials, the inhibitory effect of SDEA and its four constituents (Amentoflavone, Palmatine, Apigenin, Delicaflavone) on seven CYP450 isoforms were investigated by using the established CYP450 cocktail assay based on LC-MS/MS. Methods: Appropriate substrates for seven tested CYP450 isoforms were selected to establish a reliable cocktail CYP450 assay based on LC-MS/MS. The contents of four constituents (Amentoflavone, Palmatine, Apigenin, Delicaflavone) in SDEA were determined as well. Then, the validated CYP450 cocktail assay was applied to test the inhibitory potential of SDEA and four constituents on CYP450 isoforms. Results: SDEA showed strong inhibitory effect on CYP2C9 and CYP2C8 (IC50 ≈ 1 μg/ml), moderate inhibitory effect against CYP2C19, CYP2E1 and CYP3A (IC50 < 10 μg/ml). Among the four constituents, Amentoflavone had the highest content in the extract (13.65%) and strongest inhibitory effect (IC50 < 5 μM), especially for CYP2C9, CYP2C8 and CYP3A. Amentoflavone also showed time-dependent inhibition on CYP2C19 and CYP2D6. Apigenin and Palmatine both showed concentration-dependent inhibition. Apigenin inhibited CYP1A2, CYP2C8, CYP2C9, CYP2E1 and CYP3A. Palmatine inhibited CYP3A and had a weak inhibitory effect on CYP2E1. As for Delicaflavone, which has the potential to develop as an anti-cancer agent, showed no obvious inhibitory effect on CYP450 enzymes. Conclusion: Amentoflavone may be one of the main reasons for the inhibition of SDEA on CYP450 enzymes, the potential HDI should be considered when SDEA or Amentoflavone were used with other clinical drugs. On the contrast, Delicaflavone is more suitable to develop as a drug for clinical use, considering the low level of CYP450 metabolic inhibition.